Multi-Modality Detection Methods for Work Related Musculoskeletal Disorders (WMSD) - Elashmawy, Mohamed Ahmed (IRC, 2019)

(untitled)
Work-related musculoskeletal disorders (WMSDs) are a group of painful disorders of muscles, tendons, and nerves. Through constant and repetitive motion workers could end up sustaining injuries and developing painful symptoms, while carrying out work related activities. More notably, increased muscle fatigue over time, in which could decrease the productivity of the injured worker. Magnetic resonance imaging (MRI) and Computed tomography (CT) scans are the most prevalent methods of diagnosing and monitoring patients with WMSDs. However, Both MRI and CT are costly methods, while also having a low level of accessibility in some areas around the globe. In this research project, we are out to find if we can diagnose and monitor WMSDs using a thermal camera. An experiment of monitoring a subject utilizing a thermal camera assisted by a wireless EMG system in 2 different typing positions is conducted. Through the collected data and findings of this experiment, it is to be determined whether thermography can distinguish between ergonomic and non-ergonomic